Pengaruh Layanan Informasi Pendekatan Behavioral Terhadap Sikap Anti Bullying pada Siswa Mas Washliyah 12 Perbaungan Serdang Bedagai - Desy Novianti; Ika Sandra Dewi (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study aims to determine the effect of informational services using a behavioral approach on students’ anti-bullying attitudes at SMAS 12 Al-Jam’iyatul Washliyah Perbaungan. The background of this research is the ongoing presence of bullying behavior in schools, which negatively affects students’ social and emotional development. The research employs a quantitative approach with a quasi-experimental method and a one-group pretest-posttest design. The sample consisted of 31 eleventh-grade students selected through purposive sampling based on a tendency to exhibit bullying behavior. The research instrument used was an anti-bullying attitude questionnaire, which had been tested for validity and reliability. The results showed an increase in anti-bullying attitudes after students received informational services with a behavioral approach. This was supported by a t-test analysis, which showed a t value of 30.49 > t table at a significance level of 0.05, indicating a significant effect. It can be concluded that informational services using a behavioral approach are effective in improving students’ anti-bullying attitudes. Therefore, this approach is recommended for school counselors as a preventive strategy to address bullying behavior in schools.